Dostoevsky's Shadows - Ioana Cristina Nicolae (Centre for Behaviour and Wellness Advocacy, 2016)
In this paper, I bring to light Jung's Shadow archetype in Dostoevsky's works and also analyzes their implications in the structure of his characters. Taking into account that the Russian writer's creation is vast, I shall select a limited number of his works, namely 'The Possessed'; 'Crime and Punishment'; 'The Brothers Karamazov'; 'Notes from Underground' and 'The Double'. We are all burdened with our Shadow and must strive to overcome it, but what happens if we fail or never even try to master it? Raskolnikov's attempt to free himself from the chains of his Shadow was too late, he had already committed the murder, but not in vain, he succeeded in redeeming himself, and so his effort must be taken into account. This does not help him to avoid the punishment, but offers him a chance after serving it. On the other hand, Smerdyakov's case is different: he made no attempt to overcome his Shadow, the only argument that he brought in his favor being that he acted fuelled by the desire of fulfilling his brother's wish. It is clear that, he has no chance for a better future and the fault lies with him because he did not create that chance. Dostoevsky's characters always seem to be ruled by a tragic destiny, an unlucky fate from which they cannot escape.